Arthroscopic Iliopsoas Fractional Lengthening After Total Hip Arthroplasty: Utilization of the Iliopsoas Air Bursogram Technique for Safe and Efficient Access - Karissa N. Simon BS; Fabien Meta MD; Zachary C. Reuter MD; Aaron J. Krych MD; Bruce A. Levy MD; Mario Hevesi MD, PhD (SAGE Publishing, 2024)
Background: Patients with persistent symptomatic iliopsoas tendonitis following total hip arthroplasty may benefit from iliopsoas fractional lengthening. We present an arthroscopic approach utilizing an air bursogram that provides safe and predictable access to the iliopsoas tendon for efficient tendon lengthening without violating the capsule or unintentional instrumentation of the nearby medial neurovascular bundle. Indications: Arthroscopic iliopsoas fractional lengthening is indicated for patients with clinical evidence of symptomatic iliopsoas tendonitis following total hip arthroplasty and have no radiographic evidence of frank acetabular malpositioning. A diagnosis of iliopsoas tendinitis amenable to surgical management can be established with substantial but nondurable relief following image-guided anesthetic injection to the iliopsoas bursa. Technique Description: Under fluoroscopic guidance, an air bursogram is employed in the anatomic plane of the iliopsoas tendon to accurately identify its course. This allows for hip portal placement with precise subsequent instrumentation. This technique is preferred in the setting of postarthroplasty anatomy because it avoids capsular violation and the challenge of working in an altered anatomic space with a nearby, medially based neurovascular bundle. Results: Arthroscopic and endoscopic approaches to iliopsoas release have been shown to provide excellent functional and patient-reported outcomes in >85% of patients, and several studies have shown that an arthroscopic approach not only provides a less invasive technique but also results in comparable or improved clinical outcomes with lower revision rates compared to open release or acetabular cup revision. Our technique for arthroscopic iliopsoas fractional lengthening using the air bursogram is both safe and reproducible and offers distinct advantages, including maintenance of an intact capsule, visual confirmation of the correct anatomic structure to be released, and percutaneous access with standard arthroscopic access cannulas without the need for hip distraction. Conclusions: Arthroscopic fractional iliopsoas lengthening is a minimally invasive and successful treatment option for patients with persistent groin pain after total hip arthroplasty, especially without substantial acetabular component malpositioning. This technique includes using an air bursogram to safely identify and navigate to the iliopsoas tendon without violating the hip capsule, thereby reducing the risk of inadvertent instrumentation of adjacent critical neurovascular structures. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.